2008
DOI: 10.2337/db07-0990
|View full text |Cite
|
Sign up to set email alerts
|

Omentin-1, a Novel Adipokine, Is Decreased in Overweight Insulin-Resistant Women With Polycystic Ovary Syndrome

Abstract: OBJECTIVE-Polycystic ovary syndrome (PCOS) is associated with insulin resistance and obesity. Recent studies have shown that plasma omentin-1 levels decrease with obesity. Currently, no data exist on the relative expression and regulation of omentin-1 in adipose tissue of women with PCOS. The objective of this study was to assess mRNA and protein levels of omentin-1, including circulating omentin-1, in omental adipose tissue of women with PCOS and matched control subjects. Ex vivo and in vivo regulation of adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
191
7
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(245 citation statements)
references
References 19 publications
28
191
7
19
Order By: Relevance
“…8 It has also been reported that glucose treatment reduces omentin expression and secretion in omental fat tissue explants. 10 Consistent with these observations, our present data Omentin and carotid intima-media thickness R Shibata et al showed that plasma omentin levels negatively associated with glucose levels. Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…8 It has also been reported that glucose treatment reduces omentin expression and secretion in omental fat tissue explants. 10 Consistent with these observations, our present data Omentin and carotid intima-media thickness R Shibata et al showed that plasma omentin levels negatively associated with glucose levels. Our data also demonstrated that circulating omentin levels correlated inversely with creatinine levels, and positively with eGFR.…”
Section: Discussionsupporting
confidence: 92%
“…7,8 Low levels of plasma omentin are also associated with insulin resistance and endothelial dysfunction. 9,10 Thus, it is conceivable that circulating omentin is associated with obesity-linked disorders. An increase in carotid arterial intima-media thickness (IMT) is an established marker of early atherosclerosis and is predictive of future cardiovascular and stroke events.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, omentin-1 enhances insulin action and Akt phosphorylation [14]; it is inversely related to obesity [15] and is down regulated by insulin and glucose [13]. In an in vitro study to investigate the effects of omentin-1 on bone metabolism, omentin-1 reduced osteoclast formation by stimulating OPG and inhibiting RANKL production in osteoblasts [16].…”
Section: Introductionmentioning
confidence: 99%
“…We can postulate that the reduction in omentin-1 levels in subjects with MetS may be due to peripheral adiposity. Insulin resistance and hyperglycemia are the core processes and important risk factors for MetS, which significantly reduce the expression of omentin mRNA and its translation (28). Therefore, omentin-1 probably depresses the metabolic syndrome process throughout glucose metabolism normalization.…”
Section: Discussionmentioning
confidence: 99%